A simple fluorimetric method for the estimation of free 11-hydroxycorticoids in human plasma - Mattingly, D. (1962)
A simple fluorimetric method is described for measuring free 11-hydroxycorticoids in human plasma. Only 2 ml. of plasma is required for each estimation and the fluorescence is read in a standard direct reading fluorimeter. Six estimations can be completed in one and a half hours. It thus compares favourably with the methods in current use for estimating urinary steroids, and has the added advantage of not being dependent on the accurate collection of 24-hour urine samples.